New approaches and strategies in combatting criminality and managing crisis - Ebdane, Hermogenes E. Jr. (2003)
Discussion paper of Police Director General Hermogenes E. Ebdane, Jr., Chief, Philippine National Police, Conference workshop on the role of media in combatting criminality, September 5, 2002, UPAA Ang Bahay ng Alumni
Keywords: Crisis management